2003
DOI: 10.1074/jbc.m302814200
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Membrane Voltage-dependent Anion Channel Mediates Antiestrogen-activated Maxi Cl– Currents in C1300 Neuroblastoma Cells

Abstract: The cell membrane large conductance voltagedependent chloride channel (Maxi Cl ؊ channel) has been recorded in different cell types following excision of membrane patches or stimulation by antiestrogens under whole-cell recording conditions. However, both its molecular nature and relevance to cell physiology await elucidation. Its electrophysiological properties resemble those of the voltage-dependent anion channel (VDAC) of the outer mitochondrial membrane. This observation has led to the controversial hypoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 30 publications
4
49
2
Order By: Relevance
“…Taken together, the electrophysiological data ((1) large conductance of about 400 pS, (2) bell-shaped open probability curve, and (3) Cl À selectivity) suggest that the largeconductance channel in the plasma membrane described here is similar to the VDAC, normally present in the mitochondrial outer membrane. 13 Although there are certain differences between our observations and the reported properties of VDAC, [13][14][15][16][17][18][19] this variability may be ascribed to differences in experimental preparations and conditions. For instance, the difference in the (main state) conductance between cellular preparations and VDACs reconstituted in black lipid bilayer depends on different salt concentrations (140 mM vs 1 M).…”
Section: Vdac Is Activated During Apoptosiscontrasting
confidence: 79%
“…Taken together, the electrophysiological data ((1) large conductance of about 400 pS, (2) bell-shaped open probability curve, and (3) Cl À selectivity) suggest that the largeconductance channel in the plasma membrane described here is similar to the VDAC, normally present in the mitochondrial outer membrane. 13 Although there are certain differences between our observations and the reported properties of VDAC, [13][14][15][16][17][18][19] this variability may be ascribed to differences in experimental preparations and conditions. For instance, the difference in the (main state) conductance between cellular preparations and VDACs reconstituted in black lipid bilayer depends on different salt concentrations (140 mM vs 1 M).…”
Section: Vdac Is Activated During Apoptosiscontrasting
confidence: 79%
“…This hypothesis has received a great attention and considered to be an established concept in the field. Consistent with this idea, several groups have indeed reported the presence of VDAC protein in the plasma membrane of various cells [38,49,88,110, [110]. These authors identified an alternative first exon in the murine vdac1 gene that encodes a leader peptide at its N-terminus.…”
Section: Puzzle Of the Molecular Identity Of The Maxi-anion Channelsupporting
confidence: 55%
“…These biophysical properties are similar to those of the voltage-dependent anion channel (VDAC, also called porin) expressed in the outer membrane of mitochondria [150][151][152]. Therefore, it has been widely held that VDAC located in the plasma membrane (pl-VDAC) is the most likely candidate protein [38,45,46,49,88,110]. This hypothesis has received a great attention and considered to be an established concept in the field.…”
Section: Puzzle Of the Molecular Identity Of The Maxi-anion Channelmentioning
confidence: 93%
See 1 more Smart Citation
“…Okada has presented evidence that the maxi anion conductance (VDAC-like-VDACL) is a plasma membrane ATP-conductive pore in mammary cancer cells [70] and in macula densa cells [44], and follow-up work shows that this conductance is inhibited by internal arachidonic acid [71]. VDAC is a mitochondrial ATPpermeable membrane pore, but has been suggested also to be present in the plasma membrane as a specific splice variant (pl-VDAC-1) [72]. Interestingly, VADC-1 knockout mouse tissue shows reduced mechanically stimulated ATP release and, vice versa, overexpression of pl-VDAC-1 protein in fibroblasts leads to increased mechanically stimulated ATP release [73].…”
Section: Cell Swelling-activated Anion Conductancementioning
confidence: 99%